The comparison of balancing between male and female student at Faculty of Sports Science in Chulalongkorn University / Risyadinie Rasyiqah Razmi … [et al.] - Razmi, Risyadinie Rasyiqah; Kusrin, Jamiaton; Raja Azidin, Raja Mohamed Firhad; Mohamed Shapie, Mohamad Nizam; Boonrod, Wanchai (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2018)
Balance can be defined as the state of having weight spread equally so that it will not fall, balance is the ability to move or to remain in a position without losing control or falling. The objective of this study is to investigate whether any gender differences exist in balance performance during quiet one leg standing among Chulalongkorn University (CU) students. This study is an experimental research design. An experimental study been used to test the hypothesis in this study. In this study, the independent variable is gender while the dependent variable is the balancing. The controlled variable is the subject must first do helicopter spinning for 5 complete rounds before proceeding to the balancing test. The samples are from the students of Faculty of Sports Science in Chulalongkorn University. Based on the Cohen’s table, total sample size for this study is 34 students which consist of 17 females and 17 males. The sampling method will be used is purposive non-random sampling. The experiment results collected and the score recorded. The SPSS Statistics version 20.0 be used for all statistical analysis. The results be analyzed using an Independent Sample t-test analysis to find out whether there is a balance difference among the gender. The dependent variable is numerical and the observation is independent. The distribution data is normal which is based on Central Limit Theorem (CLT) n>30. Descriptive analysis used to assess mean and standard deviation (SD) of all the variables. There is an equal score for both gender; male and female in overall stability index. For normal score, both male and female get 6 out of 17 while 11 out of 17 of both genders obtained a good score which is better than the norms.